Developing the quality of early childhood mentoring institutions - Sri Hartini (Graduate School, Universitas Negeri Yogyakarta, 2017)
The study was to uncover the concept of quality improvement, the supporting and the inhibiting factors within the quality improve and the quality improvement in the early childhood mentoring institutions/kindergarten. The study was a qualitative research. The subjects in the study were kindergarten principals, kindergarten teachers and parents. The data were gathered by means of observation, interview and documentation. For the data analysis, the researcher selected the qualitative descriptive data analysis method. The results of the study were as follows. First, the concept of educational quality improvement in the early childhood mentoring institutions/ kindergarten has been improveed from the vision, the mission and the objectives and the concept includes the aspects of planning, process and output which has synergy from one to another. The planning has been formulated in the curriculum, the syllabus and the daily activity plan. Second, the approach, the strategy and the technique of quality improvement has maximized the well-qualified schools’ resources, have been supported by the sufficient facilities and have been funded by the sufficient budget. Third, the supporting factors within the quality improvement of early childhood mentoring institutions/kindergarten have been the increasing awareness within the society toward the significance of early childhood mentoring institutions, the massive socialization conducted by the Office of Education through the provision of training programs in relation to the early childhood mentoring institution/kindergarten management and the human resources empowerment toward developing the quality of early childhood mentoring institutions. Fourth, the inhibiting factors within the quality improvement of early childhood mentoring institutions have been the lack of society care and participation, the less quality human resources that early childhood mentoring institutions have, the fund limitation, the facility limitation and the lack of program management effectiveness.Keywords: development, educational quality, kindergarten